A novel chiral GC/MS method for the analysis of fluoxetine and norfluoxetine enantiomers in biological fluids - Janet Mifsud; Lino J Sghendo (Wolters Kluwer Medknow Publications, 2012)
Aims: A novel robust chiral gas chromatographic/mass spectrometric (GC/MS) method for the separation and measurement of fluoxetine and norfluoxetine enantiomers in urine and plasma was developed. Materials and Methods: The drug was extracted from the samples by a liquid-liquid technique, using chloroform, and the enantiomers were separated and measured on a chiral gas chromatographic column (HYDRODEX β-6TBDM®, 0.25 μm × 0.25 mm × 50 m). GC/MS instrumentation was used for the acquisition of data in the electron impact selective-ion monitoring mode. Results: The ions chosen were of a mass-to-charge ratio (m/z) exactly equal to 44 units, in order to measure fluoxetine enantiomers, 134 units in order to measure norfluoxetine enantiomers, and 58 units in order to measure diphenhydramine, the internal standard. The method was found to be linear and reproducible in the 50-500 ng/mL concentration range for both urine samples and plasma samples and for both fluoxetine and norfluoxetine, with correlation coefficients ranging between 0.994 and 0.997. Conclusions: This methodology has an enormous potential for application in pharmacokinetic studies of the enantiomers of fluoxetine